2020
DOI: 10.2147/ppa.s275783
|View full text |Cite
|
Sign up to set email alerts
|

<p>Medication-Induced Oral Hyperpigmentation: A Systematic Review</p>

Abstract: Background: Medication-induced oral hyperpigmentation is an oral condition that impacts patients' quality of life and has been linked to many systemic therapeutic agents. The exact pathogenesis of tissue pigmentation varies greatly and is not completely known. This systematic review aimed to present data on the causal association between medications and the development of oral/mucosal pigmentation as an adverse drug reaction. Methods: A systematic review and analysis of literature were conducted using the foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 64 publications
0
13
0
Order By: Relevance
“…In the systematic review based on case reports and series thereof published in 2020 by Binmadi et al . ( 10 ) they reported that the medication that was more frequently associated with these pigmentations is imatinib. The hyperpigmentation caused by this prescription has been described in several studies, such as the ones published by Mcpherson et al .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In the systematic review based on case reports and series thereof published in 2020 by Binmadi et al . ( 10 ) they reported that the medication that was more frequently associated with these pigmentations is imatinib. The hyperpigmentation caused by this prescription has been described in several studies, such as the ones published by Mcpherson et al .…”
Section: Discussionmentioning
confidence: 99%
“…There are drugs identified in systematic reviews as inductors of oral pigmentation, but they do not have this ADR registered in their SCP and that is the reason why we could not find them in our search. Among them we can highlight: golimumab, whose SCP does not mention hyperpigmentation neither in the oral cavity nor in the skin ( 15 ); ketoconazole, not described in any SPC ( 10 ); amlodipine, whose SPC only describes change of pigmentation on the skin ( 34 ); retigabine, an antiepileptic drug which has not been commercialised in Europe since 2018; clofazimine, an antileprotic whose SPC is only associated with skin lesions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Hyperpigmentation is a common condition characterized by skin darkening due to the overproduction of the pigment melanin. It has many causes including excessive sun exposure (solar lentigo), 1 changes in female hormones (melasma), 2 acne (post‐inflammatory hyperpigmentation), 3 and certain medications (minocycline) 4,5 . Hyperpigmentation is a cosmetic concern that can have a significant impact on self‐esteem and quality of life 6‐8 and is more prevalent among dark‐skinned individuals although most skin types can be affected 9‐11 .…”
Section: Introductionmentioning
confidence: 99%